Metagenomic of Actinomycetes Based on 16S rRNA and nifH Genes in Soil and Roots of Four Indonesian Rice Cultivars Using PCR-DGGE - . Mahyarudin; Iman Rusmana; Yulin Lestari (HAYATI Journal of Biosciences, 2015)
The research was conducted to study the metagenomic of actinomycetes based on 16S ribosomal RNA (rRNA) and bacterial nifH genes in soil and roots of four rice cultivars. The denaturing gradient gel electrophoresis profile based on 16S rRNA gene showed that the diversity of actinomycetes in roots was higher than soil samples. The profile also showed that the diversity of actinomycetes was similar in four varieties of rice plant and three types of agroecosystem. The profile was partially sequenced and compared to GenBank database indicating their identity with closely related microbes. The blast results showed that 17 bands were closely related ranging from 93% to 100% of maximum identity with five genera of actinomycetes, which is Geodermatophilus, Actinokineospora, Actinoplanes, Streptomyces and Kocuria. Our study found that Streptomyces species in soil and roots of rice plants were more varied than other genera, with a dominance of Streptomyces alboniger and Streptomyces acidiscabies in almost all the samples. Bacterial community analyses based on nifH gene denaturing gradient gel electrophoresis showed that diversity of bacteria in soils which have nifH gene was higher than that in rice plant roots. The profile also showed that the diversity of those bacteria was similar in four varieties of rice plant and three types of agroecosystem. Five bands were closely related with nifH gene from uncultured bacterium clone J50, uncultured bacterium clone clod-38, and uncultured bacterium clone BG2.37 with maximum identity 99%, 98%, and 92%, respectively. The diversity analysis based on 16S rRNA gene differed from nifH gene and may not correlate with each other. The findings indicated the diversity of actinomycetes and several bacterial genomes analyzed here have an ability to fix nitrogen in soil and roots of rice plant.